Facile synthesis of low band gap ZnO Microstructures - Ovando Medina, V. M.; Farías Cepeda, L.; Pérez Aguilar, N. V.; Rivera de la Rosa, Javier; Martínez Gutiérrez, H.; Romero Galarza, A.; Cervantes González, E.; Cayetano Castro, N. (Academia Mexicana de Investigación y Docencia en Ingeniería Química, 2018)
Abstract In this work a simple chemical route was employed to synthesize ZnO microparticles by precipitation from aqueous solution of ZnCl2 as precursor, NaOH as oxidizing and sodium dodecyl sulfate (SDS) as surfactant. Samples of ZnO microparticles were analyzed by scanning electron microscopy (SEM), FTIR spectroscopy, Raman spectroscopy, X-Ray diﬀraction, UV/Vis-NIR diﬀusereﬂectance,highresolutiontransmissionelectronmicroscopy(HR-TEM),andN2 adsorption-desorption.Itwasobserved from SEM analysis that ZnO microparticles with morphologies resembling six-blade impeller with diameters in the range of 500 nm to 1 m, and sheet-like (approximately 200 nm×300 nm) were obtained through this technique. X-Ray diﬀraction and Raman analyses conﬁrmed the obtaining of hexagonal wurtzite ZnO crystal structure. The calculated band gap energy was 3.19 eV, which is slightly lower than the average value reported in the literature. Speciﬁc BET area of ZnO microparticles was 26.5 m2/g. Keywords: ZnO, microstructures, band gap energy, SEM, morphology.